La historiografía inmediata española a través de Historia a Debate - San Martin, Israel (2006)
The article makes a general photography of the situation of the Spanish immediate historiography from the characteristics of the Spanish Transition to the democracy. The article show some general aspects of the development of the Spanish historiography, and the methodology used allows to detect some of the present tendencies that are being developed today. History under Debate is the tendency that this paper develops with greater detail. History under Debate is a communitynetwork of historians of different universities from the five continents that they have a common ideas for developing a new historiographic paradigm. The work unites the History under Debate tendency with the Spanish historiography.